2017
DOI: 10.1177/1071100717728678
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Neurologic Injury Following Lateralizing Calcaneal Osteotomy Performed Through a Medial Approach

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…2 In addition, it should be noted that these osteotomies are technically more challenging, require a greater amount of dissection, and theoretically place more risk on the neurovascular structures including the sural nerve within the operative field and the medial neurovascular structures crossing the osteotomy. 2,9,77 Although these calcaneal osteotomies have traditionally been performed via the lateral approach, in 2017 Jaffe et al 27 retrospectively evaluated 24 patients who underwent a cavovarus reconstruction including a lateralizing calcaneal osteotomy via a medial approach. They found no incidence of postoperative tarsal tunnel syndrome or tibial nerve palsy while achieving an average translation of 11.6 mm with 83% of the osteotomies being through the middle third of the calcaneus, which has been previously reported to be a potentially higher-risk area for tibial nerve symptoms.…”
Section: Calcaneal Osteotomiesmentioning
confidence: 99%
“…2 In addition, it should be noted that these osteotomies are technically more challenging, require a greater amount of dissection, and theoretically place more risk on the neurovascular structures including the sural nerve within the operative field and the medial neurovascular structures crossing the osteotomy. 2,9,77 Although these calcaneal osteotomies have traditionally been performed via the lateral approach, in 2017 Jaffe et al 27 retrospectively evaluated 24 patients who underwent a cavovarus reconstruction including a lateralizing calcaneal osteotomy via a medial approach. They found no incidence of postoperative tarsal tunnel syndrome or tibial nerve palsy while achieving an average translation of 11.6 mm with 83% of the osteotomies being through the middle third of the calcaneus, which has been previously reported to be a potentially higher-risk area for tibial nerve symptoms.…”
Section: Calcaneal Osteotomiesmentioning
confidence: 99%
“…1,2 For this reason, some authors have advocated prophylactic tarsal tunnel release, 8 and others have suggested performing the LCO itself from a medial approach. 5 Because increasing lateralization progressively restricts tarsal tunnel volume, performing wedge resections and minimizing the amount of lateralization have also been advocated. 2 Regardless of whether excessive lateralization leads to tarsal tunnel syndrome, it is still often difficult to achieve adequate valgus in patients with significant heel varus.…”
Section: Discussionmentioning
confidence: 99%
“…The special anatomical structure and soft tissue space of the ankle canal makes the ankle canal syndrome the most common disease symptom in this area, and its occurrence is often closely related to the nerve compression [2,3]. This not only leads to tibial nerve dysfunction and plantar pain, but also mainly causes heel pain and even abductor atrophy of the little toe [4].It is noteworthy that this body part is used as a pathway in minimally invasive and surgical operations [5], ankle canal decompression, ankle canal incisions, and external nail xation of fractures are likely to cause iatrogenic nerve injury [6][7][8]. At present, through the anatomic study of the tibial nerve and its branches at the ankle canal, the location and course of the nerve are determined, and the origin and quantity of the medial calcaneus nerve and the inferior calcaneus nerve at the ankle canal are classi ed [9][10][11], which provides a great help for the understanding of the nerve in the ankle canal.…”
Section: Introductionmentioning
confidence: 99%